Efficient self-coordination in policy networks: A simulation study - Fritz W. Scharpf; Matthias Mohr (Max-Planck-Institut für Gesellschaftsforschung, 1994)
The paper begins with a reexamination of claims regarding the welfare-theoretical efficiency of various modes of non-hierarchical policy coordination which Charles Lindblom (1965) had subsumed under the label of Partisan Mutual Adjustment. It is argued that these claims are implausible if Lindblom's mechanisms of horizontal self-coordination are examined one at a time. They either will not assure significant welfare gains in the general case, or the attempt to raise the level of general welfare through self-coordination will encounter rapidly escalating transaction costs. As Lindblom had pointed out, however, several coordination methods will often be combined in real-world policy processes. The intuition that this might significantly increase the welfare efficiency of self-coordination is explored in a computer simulation study based on the game-theoretical reformulation of five simple coordination mechanisms. We can show that, in a given population of interdependent actors, Positive Coordination within relatively small coalitions who are required to obtain the agreement of outside actors through Negative Coordination and Bargaining, are able to achieve relatively high welfare gains while economizing on transaction costs. This pattern is by no means unusual in real-world policy processes. – – Der Aufsatz untersucht die Plausibilität von Behauptungen über die wohlfahrtstheoretische Effizienz von Methoden der nicht-hierarchischen Koordination politisch-administrativer Akteure, die Charles Lindblom (1965) unter dem Sammelbegriff des Partisan Mutual Adjustment zusammengefaßt hatte. Für jede einzelne dieser Methoden, so kann gezeigt werden, ist dieser Anspruch nicht generell zu begründen. Entweder können unter allgemeinen Bedingungen nur geringe Wohlfahrtsgewinne erzielt werden, oder die Koordination scheitert an eskalierenden Transaktionskosten. Allerdings hatte schon Lindblom darauf hingewiesen, daß in realen Politikprozessen typischerweise mehrere Koordinationsmethoden zugleich zum Zuge kommen. Die Vermutung, daß gerade dadurch die Wohlfahrts-Effizienz der horizontalen Selbstkoordination gesteigert werden könnte, wird hier in einer Computer-Simulationsstudie überprüft. Ausgehend von einer spieltheoretischen Rekonstruktion von fünf einfachen Koordinationsmechanismen kann gezeigt werden, daß insbesondere die Kombination von Positiver Koordination mit Negativer Koordination und mit Bargaining eine hohe Wohlfahrtseffizienz erreicht. Wenn die Mitglieder relativ kleiner Koalitionen sich intern positiv koordinieren, aber die Zustimmung der übrigen Mitglieder einer Population von interdependenten Akteuren durch Negativkoordination und Bargaining gewinnen müssen, dann können relativ hohe Wohlfahrtsgewinne bei moderaten Transaktionskosten erwartet werden. Eben dieses Muster läßt sich auch in realen Prozessen der Politikformulierung und Implementation wiederfinden.
Keywords: 300